Effects of Xinglong Hydro-Junction on nitrogen distribution in the Hanjiang River riparian zone - Shuxian CHEN; Ruihua SHANG; Yucheng FENG; Zhiqiang WANG; Teng MA (Shuiwen dizhi gongcheng dizhi, 2021)
A riparian zone, as the junction of surface water and groundwater, mainly controls the nitrogen cycle between surface water and groundwater through denitrification and other actions. Water conservancy projects will significantly change the hydrological environment of river regions, and affect the distribution and circulation of nitrogen in riparian zones. Exploring the influence mechanism of water conservancy projects on the riparian nitrogen cycle is of great practical significance for understanding the control and utilization of regional nitrogen. In this paper, the Xinglong Hydro-Junction is taken as the object, and three riparian zone sampling sections are set up in the upper and lower reaches of the project, with five sampling points in each section. TN, "tri-nitrogen" (refers to\begin{document}${\rm{NH}}_4^+ $\end{document}-N, \begin{document}${\rm{NO}}_2^- $\end{document}-N, \begin{document}${\rm{NO}}_3^- $\end{document}-N) and relevant soil physical and chemical properties are analyzed for the collected 150 soil samples. The results show that (1) the nitrogen content in the riparian sediments in the upstream of the water conservancy project is significantly higher than that in the downstream, and the average content of total nitrogen and "three nitrogen" in section A is 1.12-3.27 times that in sections B and C of the downstream. (2) The horizontal variation trend of contents of TN and "tri-nitrogen" in the riparian zones of the three sections is not consistent, showing that TN content in the same section is higher in the embankment, and the sampling point in the embankment close to the embankment is the abrupt change point (sharp increase or decrease) of "tri-nitrogen" content. (3) The vertical distribution pattern of TN and "tri nitrogen" is similar: nitrogen content decreases rapidly from 0 to 60 cm, and irregular change occurs below 60 cm. Nitrogen content decreases from top to bottom. The Xinglong Dam mainly affects its upper reaches. Through water storage, the groundwater level of the upstream riparian zone rises, and the sediments are submerged for a long time, leading to the decrease of denitrification capacity. Due to the difference in microgeomorphology caused by levee in the same section, the groundwater in the levee is deeper than that outside the levee, and the denitrification capacity of the sediments in the levee is weaker than that outside the levee.